'Heart-like' cross-sectional shape can better improve the hemodynamics in spiral laminar flow graft for small-caliber bypass application: a numerical study. Issue 13 (3rd October 2022) - Wen, Jun; Wu, Wenqing; Peng, Liqing
Abstract: Small-caliber grafts remain disappointed in the long-term bypass surgeries of coronary and peripheral arterial diseases. In order to improve the hemodynamics in small-caliber artery bypass grafts (ABGs), an improved spiral laminar flow (improved-SLF) graft with a 'heart-like' cross-sectional shape was proposed and verified by computational fluid dynamics simulation in this study. The results show that such graft can indeed induce a spiral flow and enhance the WSS distribution on the graft section. Furthermore, the helically distributed ribbon of unfavorable WSS observed in the original SLF graft was eliminated in the improved-SLF graft due to its smoothed and gentle helical ridge. On the other hand, improved-SLF ABG improved the WSS distribution in the distal anastomosis as well, because it maintained the strength of spiral flow when entering the anastomosis region. Finally, the improved-SLF ABG slightly increased the pressure drop along the bypass due to its small change of the general graft structure. As a proof-of-concept study, it can be concluded that improved-SLF graft can not only evenly enhance the WSS distribution in the graft section, but also improve the hemodynamic environment in the distal anastomosis without significantly increasing the pressure drop along the bypass, indicating such new helical-type graft may be more suitable to be used in the small-caliber graft bypass surgeries.